A Comparative Financial Liquidity Analysis of Fatima and Fauji Fertilizer Companies Limited (Journal of Asian Development Studies, 2024)
The primary purpose of this research is to reasonably study the liquidity position of two major organizations in the fertilizer sector, namely Fatima and Fauji Fertilizer Companies Limited. The annual secondary panel data was taken from 2010 to 2018. For that, annual published reports were collected from the official website of the State Bank of Pakistan. The Excel tool analyzed the data through tables and bar graphs. However, the results concluded that the financial position of Fauji fertilizer was better in terms of liquidity management than Fatima fertilizers. Therefore, Fatima Fertilizer is advised to improve its liquidity position, which may simultaneously reduce its business risk. Otherwise, it will be damaging to its business. However, liquidity plays an essential role in business,so both companies must invest in the most liquid assets, such as the T-bills and other marketable securities, to improve their liquidity position. Finally, both companies must try to improve their net profit as well.